International Multi-Conference on Systems, Sygnals &Amp; Devices 2012
DOI: 10.1109/ssd.2012.6198102
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube composite for application in gait analysis

Abstract: Ulceration as a complication of diabetes mellitus is caused by high recurrent pressures at the foot, which may even lead to amputation. Risk factors of diabetic foot ulcers are diabetes, polyneuropathy and obesity. A gait analysis study including healthy, obese and diabetic persons was accomplished to determine characteristic plantar pressure distribution patterns between these groups. By analyzing the resulting roll-overpatterns, it should be possible to derive better sensor design criteria for new pressure s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…According to the percolation theory 32 and general effective media theory 33,34 , the compressed nanocomposites increase the amount of conductive and percolating paths 35 . The volume resistance R v is defined as 36 :…”
Section: Materials and Methods Design Of The Sensor Arraymentioning
confidence: 99%
“…According to the percolation theory 32 and general effective media theory 33,34 , the compressed nanocomposites increase the amount of conductive and percolating paths 35 . The volume resistance R v is defined as 36 :…”
Section: Materials and Methods Design Of The Sensor Arraymentioning
confidence: 99%
“…In 2012 Gerlach et al [66] used a different approach, exploiting materials research to use a composite of multiwall carbon nanotube (CNT) and polydimethylsiloxane (PDMS) to make a single axis pressure sensor for plantar pressure measurement. This work was expanded in 2015 to a sensing matrix capable of tracking the pressure distribution across the entire plantar surface [43].…”
Section: A Resistive Sensorsmentioning
confidence: 99%
“…In resistive sensors, Wang et al explored the possibility of plantar pressure measurement by employing carbon coatings between tooth-shaped conversion layers [11]. Gerlach et al in their work, showed the implementation of Carbon Nanotubes (CNT) and Poly-di-methyl-siloxane (PDMS) for plantar pressure computation [12]. Resistive sensors are widely used for their low cost but, they suffer from EMI, low sensitivity, and repeatability.…”
Section: Introductionmentioning
confidence: 99%